The effects of different solvent extraction and pH on the stability of carotenoids and chlorophyll in Cucumis melo L. for potential coating technology - Che Musa, Siti Aisha Na'illa; Taha, Rosna Mat; Abdul Razak, Ummi Nur Ain; Anuar, Nordiyanah; Arof, Abdul Kariem (Emerald, 2018)
Purpose: The purpose of this paper is to evaluate the potential use of natural colorant extracted from fruit flesh and leaves of Cucumis melo L. (C. melo L.) in coating applications. Design/methodology/approach: Carotenoids and chlorophylls compounds were extracted from C. melo L. fruit flesh and C. melo L. leaves with the best extraction solvents. Both compounds were tested at various pH for colour stability tests. Then, the most stable pH of both extracts was mixed with 20 per cent poly methyl methacrylate (PMMA) together with tetrahydrofuran and acrylic polyol to form a coating system on glass slides. The coated glass slides were exposed to three different temperatures. The effects of heat on the coated glass slides were evaluated using spectrophotometer at 400-700 nm wavelengths. Findings: Results revealed that carotenoids extracted from C. melo L. were less stable to be applied in coating applications since the colour degraded in a very short time; however, the chlorophylls extracted were more stable where the colour retained for longer duration. Originality/value: The method of the plant pigment production of C. melo L. with PMMA was a modified method that could give other various applications as natural product based on plant pigments.